Adrenomedullin as a Growth and Cell Fate Regulatory Factor for Adult Neural Stem Cells. (24th September 2012) - Martínez-Herrero, Sonia; Larráyoz, Ignacio M.; Ochoa-Callejero, Laura; García-Sanmartín, Josune; Martínez, Alfredo
Abstract : The use of stem cells as a strategy for tissue repair and regeneration is one of the biomedical research areas that has attracted more interest in the past few years. Despite the classic belief that the central nervous system (CNS) was immutable, now it is well known that cell turnover occurs in the mature CNS. Postnatal neurogenesis is subjected to tight regulation by many growth factors, cell signals, and transcription factors. An emerging molecule involved in this process is adrenomedullin (AM). AM, a 52-amino acid peptide which exerts a plethora of physiological functions, acts as a growth and cell fate regulatory factor for adult neural stem and progenitor cells. AM regulates the proliferation rate and the differentiation into neurons, astrocytes, and oligodendrocytes of stem/progenitor cells, probably through the PI3K/Akt pathway. The active peptides derived from the AM gene are able to regulate the cytoskeleton dynamics, which is extremely important for mature neural cell morphogenesis. In addition, a defective cytoskeleton may impair cell cycle and migration, so AM may contribute to neural stem cell growth regulation by allowing cells to pass through mitosis. Regulation of AM levels may contribute to program stem cells for their use in medical therapies.